Carcinoma basocelular en nariz de paciente interno en un centro penitenciario (2016)
Introduction. Basal cell carcinoma is the most common malignant skin tumor, depending on its aggressiveness it can metastasize.Clinical case. Male patient sent to prison with an injury of years of evolution in left nasal region ulcerated and diagnosed as basal cell carcinoma without metastasizing. It was treated with radical radiotherapy achieving complete remission.Discussion. There are several treatment options, surgery being the most effective one. What it is important for the primary care physician is to know the differential diagnosis of other benign lesions, to monitor and to keep updated on therapeutic alternatives.